High-level mosaic trisomy 14 at amniocentesis in a pregnancy associated with congenital heart defects and intrauterine growth restriction on fetal ultrasound - Chih-Ping Chen; Fang-Tzu Wu; Liang-Kai Wang; Yen-Ting Pan; Meng-Shan Lee; Wayseen Wang (Elsevier, 2023)
Objective: We present high-level mosaic trisomy 14 at amniocentesis in a pregnancy associated with congenital heart defects (CHD) and intrauterine growth restriction (IUGR). Case report: A 34-year-old, primigravid woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. This pregnancy was conceived by in vitro fertilization and embryo transfer (IVF-ET). Amniocentesis revealed a karyotype of 47,XX,+14[9]/46,XX[13], consistent with 40.9% (9/22 colonies) mosaicism for trisomy 14. Simultaneous array comparative genomic hybridization (aCGH) on the DNA extracted from uncultured amniocytes revealed 61% mosaicism for trisomy 14. Prenatal ultrasound at 22 weeks of gestation showed a malformed fetus with double outlet of right ventricle (DORV), ventricular septal defect (VSD), pulmonary stenosis and severe IUGR with the growth parameters equivalent to 18 weeks of gestation. The pregnancy was terminated at 23 weeks of gestation, and a 278-g female fetus was delivered with facial dysmorphism of hypertelorism, low-set small ears and wide depressed nasal bridge. Quantitative fluorescent polymerase chain reaction (QF-PCR) analysis on the DNA extracted from parental bloods, cord blood, umbilical cord and placenta confirmed a maternal origin of the extra chromosome 14 and excluded uniparental disomy (UPD) 14. The umbilical cord had a karyotype of 47,XX,+14[7]/ 46,XX[13], and the placenta had a karyotype of 47,XX,+14[4]/46,XX[36]. Conclusions: High-level mosaic trisomy 14 at amniocentesis can be associated with abnormal ultrasound findings of CHD and IUGR.